Institutional interconnections and cross-boundary cooperation in inclusive business : case studies from India and Africa - Okada, Yoshitaka; Stanislawski, Sumire (Emerald Publishing Limited, 2021)
The success or failure of inclusive business often depends on institutional interconnections. By examining case studies of inclusive business projects in India and several African nations, Institutional Interconnections and Cross-Boundary Cooperation in Inclusive Business asks how these connections can be developed to help alleviate poverty through business activities in developing countries. Conceptual orientations of what inclusion means can act to restrict the value orientation of an inclusive business project and its management practices. A significant approach of this book is an understanding that the economically disadvantaged have their own institutions to which they credibly commit, and that they are important, valuable, and dignified stakeholders or partners in an inclusive business project. By giving more weight to these institutions, it is possible to understand that some local companies may engage in inclusive practices by involving these actors as part of their regular business activities. Using concepts of mainstream, marginalized, and hybrid inclusion, this book explores the nature and characteristics of institutional interconnections in inclusive business in a study that will appeal to researchers and practitioners of strategy, international business, and corporate social responsibility.